MOBILE JOURNALISM PADA PRODUKSI MATERI BERITA KOMPASTV - Alvian Dwi Putranto; Irwansyah (Jurnal Spektrum Komunikasi, 2022)
The digital era as it is today makes humans able to take advantage of various existing technologies to facilitate their work, including in the field of journalism. Mobile journalism is a video journalism practice that only relies on mobile devices and various accessories. KompasTV as news television is also trying to optimize mobile journalism to produce news material. This study aims to determine how the implementation of mobile journalism in the production of news material and its relationship to the speed and quality of KompasTV news broadcasts. The method used is literature review, interviews and also observation. The results of this study are that mobile journalism can increase the reactivity of journalists to events so that the actuality of the news will increase. There is a significant reduction in cost but also in quality of impressions. Mobile journalism has advantages and disadvantages, but this depends on how a journalistic media organization can work around it so that there is a balance between the speed of news delivery and the quality of the impressions.